"An in vitro study to evaluate apical sealing ability of two types of resin based epoxy sealers" (Journal of Hama University, 2020)
This study aimed to investigate the apical sealing ability of the resin based epoxy sealers Ah plus and Adseal. The sample consisted of 42 human teeth single root of type I, untreated, does not show any fracture and does not exceed the apical diameter of the size # 25. The sample has been randomly divided into two experimental groups and two negative and positive control. The 1st group consisting of 15 teeth were obturated with GP cones with AH sealer, while the 2nd group consisting of 15 teeth were filled with GP cones with Adseal sealer, and then the area surface of tooth was coated with two layers of nail varnish. All surface area of the teeth were coated except the very last 2mm of the apex. The samples were stained with a methylene blue solution 2% for 24 hours and longitudinal sections were performed to investigate dye leakage starting from the apical limits of obturation. The study showed that the dye leakage rate in the first group was 2.07 ± 0.71 mm While the dye leakage rate in the second group was 2.40 ± 0.67 mm. there was no important statistical significance in apical leakage rate between Ah plus  and Adseal.